Effect of Glittering and Reflective Objects of Different Colors to the Output Voltage-Distance Characteristics of Sharp GP2D120 IR - Mohd Rusdy , Yaacob; Anuar , Mohamed Kassim; Nik Syahrim , Nik Anwar (ACEEE, 2012)
This paper presents a study on the effect of glittering and reflective objects with different colors to the output voltage-distance characteristics of Sharp GP2D120 IR Sensor, which operates by employing the principle of single point triangulation. The study was conducted by using a compact disk and plastic materials with four different colors, in which the distance for each of them was measured by a Sharp GP2D120 IR Sensor mounted on a constructed experimental setup. The results obtained shows the output-voltage-distance characteristics which indicate that; the white color plastic is having the highest level of reflectivity, followed by gray, transparent and black color objects, and compact disk as a glittering object is seemed to be having the lowest level of reflectivity.